Influence of historical events on construction of temples in Kyiv till 1917 - Bachynska, Olga (КНУБА, 2017)
Kyiv is ancient city with a unique history. A huge role in its development the temples have played [19]. Down to ХХ of century they influenced formation of city structure, appearance of building, general impression from urban environment and life of the population. In ХХ century the most part of temples was destroyed, the ancient town planning structure is destroyed too [3]. But the historical past continues to influence life of modern Kyiv today.
Keywords: history, Kyiv; influence of historical events; period; a temple.; 726.1(477.411)"10"/"19"